Literasi Digital dalam Pembentukan Self-Esteem dengan Berwawasan Kebangsaan Nasional di Sekolah Teman Belajar Cipinang Jakarta Timur - Murtanti Putri, Dianingtyas; Azhari, Sharon; Santoso, Berkah I.; Puti, Azura; Widiastuti, Tuti (Indonesian Journal for Social Responsibility, 2021)
Advances in digital technology during the Covid-19 pandemic turned out to have an important role in communication and information. However, the limited space for movement due to the extended PPKM provides opportunities to access social media in a short time. The intensity of using social media for too long can affect the mental health of themselves not only in adolescents, it can also affect children at an early age. This Community Service Activity (PkM) was carried out at the Sekolah Teman Belajar, Cipinang East Jakarta, where there was still a lack of knowledge about the use of social media and lack of awareness of parents in assisting their children. The purpose of the service activities carried out is to provide understanding through digital literacy methods in the formation of self-esteem with national insight. The implementation method is carried out in the form of providing assistance and training to students by involving the parents of students. Then, provide an understanding of digital parenting, where as parents must also follow the development of content packaged through social media. In addition, students who are still at an early age are introduced to wayang characters, namely Arjuna and Srikandi which are packaged through animated videos. The results of the activity showed that the participants understood the explanation given by the facilitator. Then with an interactive experience sharing approach that implements 5W + 1H there is self-disclosure to students, in this case they want to make story ideas which later on from the results of the story ideas are depicted in the animated video of Arjuna and Srikandi as icons of my friends. The process of making story ideas is a process of forming self-esteem, then participants are equipped to invite families to create entertaining content by raising cultural values as the theme on both TikTok and Instagram, this aims as an effort to form national identity.